2010
DOI: 10.1080/00071668.2010.528752
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of aflatoxin B1 by turkey liver microsomes: responsible cytochrome P450 enzymes

Abstract: 1. A study was conducted to determine the cytochrome P450 enzymes responsible for the bioactivation of aflatoxin B1 into its epoxide form (AFBO) in turkey liver microsomes. 2. The strategies used included the measurement of prototype substrate activity for specific human P450s, use of selective inhibitors, determination of correlation between aflatoxin bioactivation and enzymatic activity of prototype substrates and the determination of immunoreactive proteins using antibodies against human P450s. 3. Enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Hence, liver is the target organ for AF toxicity (Diaz et al, 2010 andMurcia et al, 2011). Dlimonene, a monoterpenoid constituent of citrus fruit oil (CFO) has inhibitory effects on cytochrome P450 enzymes, p-nitrophenol hydroxylase (pNP) and 7-ethoxyresorufin O-deethylase (EROD) activity in-vitro in liver microsomes, prevents bioactivation of procarcinogens and blocks tumour induction by chemical carcinogens (Reicks and Crankshaw, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, liver is the target organ for AF toxicity (Diaz et al, 2010 andMurcia et al, 2011). Dlimonene, a monoterpenoid constituent of citrus fruit oil (CFO) has inhibitory effects on cytochrome P450 enzymes, p-nitrophenol hydroxylase (pNP) and 7-ethoxyresorufin O-deethylase (EROD) activity in-vitro in liver microsomes, prevents bioactivation of procarcinogens and blocks tumour induction by chemical carcinogens (Reicks and Crankshaw, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In regards to CYP3A4, Klein et al (2000) found that this enzyme plays a minor role in the bioactivation of AFB1 in turkeys. This finding, however, could not be substantiated by Diaz et al (2010a) who found no correlation between nifedipine oxidation (an indicator of CYP3A4 activity) and AFBO formation, and no effect on AFBO formation when the prototype inhibitor of human CYP3A4 activity troleandomycin was used. Induction of CYP3A4 activity by BHT in turkeys (as evidenced by increased nifedipine oxidation) was correlated with decreased in vivo adverse effects of AFB1 (Guarisco et al, 2008), which further supports the notion that CYP3A4 is not involved in AFB1 bioactivation in turkeys.…”
Section: Wwwintechopencommentioning
confidence: 40%
“…This enzyme was suggested to correspond to the human ortholog CYP1A2 (Yip & Coulombe, 2006). However, using human prototype substrates and inhibitors, Diaz et al (2010a) found evidence for AFB1 bioactivation by CYP1A1 but not by CYP1A2 in turkey liver microsomes. Interestingly, the turkey CYP1A5 has a high amino acid sequence homology not only with the human CYP1A2 (62%) but also with the human CYP1A1 (61%) as reported by the UniProtKB database (http://www.uniprot.org) and the National Center for Biotechnology Information database (http://www.ncbi.nlm.nih.gov).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations